MEMBANGUN PERADABAN DUNIA BERBASIS ISLAM BERKEMAJUAN - Zulkifli, Zulkifli; Elhusen, Shofwan Karim; Asmaret, Desi; Lahmi, Ahmad; D, Dasrizal (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2025)
Islam is a religion that has a clear direction for the future, but how progress in the future has not been found qualified studies. Therefore, this paper aims to describe Islam for World Civilization. World civilization is a view that prioritizes the integration of Islamic values with the principles of modern progress in various aspects of life. This research aims to explore and analyze the contribution of Islam in building a more just and harmonious world civilization. This research is qualitative in nature using explorative and analytical methods. In general, the result of this research is that Islam is a religion that teaches a central attitude so that its people actively look at their lives with faith and a positive attitude. This progressive Islam means Islam that brings its followers to a better life, which is open and strives to always be better by adopting movements that can lead humans to progress. The progress of Islam must be encouraged by Muslims who must always return to the teachings of Islam, namely the Al-Quran and Hadith. The implication of this research is the need for further development and dissemination of the concept of Islam Berkemajuan in various fields of life. Governments, educational institutions, and civil society organizations can play an important role in supporting initiatives that promote the principles of Islam Berkemajuan. Thus, Islam Berkemajuan can be an effective model in building a more just, prosperous, and harmonious world civilization.